2019
DOI: 10.1002/acn3.740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of soluble adhesion molecules in anti‐NMDAR encephalitis patients

Abstract: Increasing evidence indicates that immune system dysfunction affects anti‐N‐methyl‐D‐aspartate receptor ( NMDAR ) encephalitis. This study aims to investigate the relationship between adhesion molecules and the pathophysiology in anti‐ NMDAR encephalitis. Soluble forms of Intercellular adhesion molecule‐1 ( sICAM ‐1), vascular adhesion molecule‐1 ( sVCAM ‐1), and L‐selectin ( sL ‐selectin), were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Our previous study showed the levels of sICAM-1, sVCAM-1 and sL-selectin in CSF were significantly elevated in anti-NMDAR encephalitis patients. Combined with our findings ( 30 ), it may share a similar pathophysiological mechanism in anti-NMDAR encephalitis. We hope to further explore this in our future research.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous study showed the levels of sICAM-1, sVCAM-1 and sL-selectin in CSF were significantly elevated in anti-NMDAR encephalitis patients. Combined with our findings ( 30 ), it may share a similar pathophysiological mechanism in anti-NMDAR encephalitis. We hope to further explore this in our future research.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, abnormal elevation of sCD146 has been reported to correlate with proinflammatory factors, such as TNF-α, IL-13 and IL-17 ( 5 , 27 ). Early research by our team confirmed that the presence of inflammatory factors in the CSF of anti-NMDAR encephalitis patients reflect the activity of the disease ( 8 , 9 , 17 , 28 30 ). In the present study, we considered that local inflammation in the brain was activated, leading to the accumulation of inflammatory factors in the CSF that enhanced the expression of sCD146, ultimately promoting BBB dysfunction.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, our research revealed that the poor prognosis of LGI1 encephalitis patients was associated with an increase in ICMA1 expression. ICAM1 is a transmembrane protein whose expression is elevated on endothelial and epithelial cells at sites of inflammation, is expressed on leukocytes and endothelial cells, and is upregulated in response to inflammatory signals [ 23 , 24 ]. ICAM1 has been linked to the pathophysiology of a number of autoimmune diseases and inflammatory syndromes, including gastric cancer, multiple sclerosis, and neuromyelitis optica [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1-/- or mutant mice exhibited less T cell infiltration in the CNS and less clinical disability in a mouse model of multiple sclerosis [ 28 ]. In the anti-NMDAR encephalitis group, CSF levels of soluble ICAM1 were significantly higher in the patient cohort [ 23 ]. Notably, a significant positive association was observed between the severity of NMDAR encephalitis and the amount of ICAM1 in CSF [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al observed BBB dysfunction based on the results of QAlb in anti-NMDAR encephalitis ( 154 ). Some chemical agents related to BBB damage and CNS inflammation are observed in the CSF and serum in anti-NMDAR encephalitis ( 155 , 156 ). Due to the impaired BBB, anti-NMDAR antibodies may transfer from pregnant C57BL/6J mice to fetuses, causing severe but reversible synaptic and neurodevelopmental alterations ( 157 ).…”
Section: Bbb Nmdars and Anti-nmdar Encephalitismentioning
confidence: 99%